Fintech for sustainable economic development in coastal areas: A bibliometric review - Sadhana, Kridawati; Sukardi; Susilo, Eko Agus; Maulana, Ilham Nur Hanifan; Nashihah, Durratun (International Journal of Innovative Research and Scientific Studies, 2025)
This paper claims that FinTech has great potential to advance coastal areas' sustainable economic growth. By enhancing financial inclusion, supporting green finance, and building a suitable legislative environment, FinTech might significantly help coastal economies to be resilient and sustainable. A bibliometric study was conducted over a 5-year period (2019–2024) utilizing criteria to select the most significant papers on absorptive capacity from two research databases, ISI Web of Science and Scopus. Drawing inspiration from the HistCiteTM and VoSviewer tools, the integration of financial technology (FinTech) into the economic frameworks of coastal communities offers a transformative opportunity for sustainable economic development. FinTech substantially improves financial inclusion, particularly in areas without conventional banking services. FinTech enables small to medium-sized organizations (SMEs) to obtain funding using digital platforms, advancing local businesses and economic sustainability. FinTech bolsters regional economic resilience and entrepreneurship, as industries like fisheries, which are susceptible to environmental variations, frequently determine the economic activity in coastal areas. The existence of FinTech in coastal communities, where sectors like fishing depend on economic activity, is vulnerable to environmental fluctuations.